Dyeing for entertainment : dyeing, painting, breakdown, and special effects for costumes - Carignan, Erin (New York, NY : Routledge, 2024)
"Dyeing for Entertainment encompasses a wide range of methods of theatrical painting and dyeing to create beautiful artistic products for theatre, film, TV, opera, and themed entertainment. Featuring examples from renowned international artisans in the field, this book provides a wealth of information on creating and changing colors, prints, and surface textures of fabric using traditional and non-traditional costume, scenic, fine-art, and metal-smithing techniques. It also includes new, safer materials and methods to minimize exposure to toxic materials and fumes. With more than 250 full-color images, this technical manual is designed to guide and inspire new artists in the collaborative art of painting, dyeing, ageing, and slinging blood and bling on costumes that is an essential part of creating characters for the entertainment industry. Written for undergraduate and graduate students of costume design and technology, professional dyers and breakdown artists, and cosplayers, this book can be used as a reference and springboard to create your own magical processes, custom fabrics, and unforgettable costumes."--Provided by publisher.
Includes bibliographical references and index.
Keywords: Theaters -- Stage-setting and scenery; Dyes and dyeing -- Technique; Costume design